The Influence of Entrepreneurship Education, Entrepreneurial Motivation, And Income Expectations on Entrepreneurial Interest - Riyanti, Yunita; Dewi, Retno Mustika (Sumber Belajar Sejahtera, 2024)
Entrepreneurship is one area that should be taken into account as a driving aspect of a country's economy. However, in reality, students are not very interested in entrepreneurship. This research aims to explain the influence of entrepreneurship education, entrepreneurial motivation and income expectations on students' entrepreneurial interest. This research used a sample of 157 students from economic education, accounting education, office administration education and business education at the Faculty of Economics and Business Universitas Negeri Surabaya. This study using causal associative research methods with a quantitative approach and multiple linear regression analysis.The results of the research show that education entrepreneurship, motivation for entrepreneurship, and income expectations simultaneously influence entrepreneurial interest. Meanwhile, partially, the results obtained were that entrepreneurship education had no effect on students' entrepreneurial interest, while entrepreneurial motivation and income expectations had an influence on students' entrepreneurial interest. In this way, the university is expected to be able to provide full support and facilities so that it can support students in learning and understanding entrepreneurship.